2017
DOI: 10.4172/2155-6156.1000741
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Magnitude, Severity and Associated Factors of Hypoglycemia in Diabetic Patients Attending National Diabetes Referral Clinic at Tikur Anbessa Hospital, Addis Ababa, Ethiopia

Abstract: Background: Hypoglycemia poses a barrier to optimum diabetes management especially among patients taking insulin therapy. However little is known about the magnitude and effect of hypoglycemia among diabetic patients in Ethiopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
3
4
0
Order By: Relevance
“…Despite its significance, the odds of suffering episodes of hypoglycemia since they were diagnosed to have T1DM were about 35% less likely in male patients compared to female patients. This result was consistent with the finding documented in the study done in Ethiopia [32]. Physiologically, there is a large sexual dimorphism in counterregulatory responses to hypoglycemia.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Despite its significance, the odds of suffering episodes of hypoglycemia since they were diagnosed to have T1DM were about 35% less likely in male patients compared to female patients. This result was consistent with the finding documented in the study done in Ethiopia [32]. Physiologically, there is a large sexual dimorphism in counterregulatory responses to hypoglycemia.…”
Section: Discussionsupporting
confidence: 93%
“…Like other evidences, this finding described as history of diabetes and events of hypoglycemia went almost parallel in patients' life. Previous studies had demonstrated that patients with more than five years of diabetes history were more likely to experience hypoglycemia events [2, 5, 20, 32, 38]. Blood glucose monitoring options had also a significant association with the events of hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…This study was in line with 50% of the RECAP-DM study in Argentina (35). This finding was lower than 86.7% in Debre Markos Referral Hospital (5), 88% in Tikur Anbessa Specialized Hospital (23), and 94.3% in St. Paul's Hospital Millennium Medical College (22) studies in Ethiopia and 91.7% from HAT study in Brazil (36), 97.1% in Colombia (37), 97.4% from an international survey in nine countries (38), and 100% from the Southeast Asia cohort of IO HAT study (39). The variation observed between this and other studies may be due to the operational definition used.…”
Section: Discussionsupporting
confidence: 89%
“…The factors associated with hypoglycemia are varied. It may include age, sex, occupational status, residence, body mass index, missed meals or inadequate caloric intake, alcohol consumption, concurrent use of an opioid, level of fasting blood sugar, blood glucose monitoring, glucose checkup period, insulin or diabetes medications, duration of diabetes, and presence of stroke (3,5,8,(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Hypoglycemia has a significant negative impact on a person’s well-being and QOL and can therefore influence adherence, compliance, and ultimately the success of the insulin therapy. In East Africa, surveys on hypoglycemia indicated high frequency episodes (T1DM, 88%; T2DM, 69%) with almost half of the study population being unaware of the hypoglycemia [ 144 ]. Efforts to avoid hypoglycemia include patient education, SMBG, and improving insulin delivery through proper delivery devices and techniques.…”
Section: Hypoglycemia Weight Gain and Psychosocial Aspectsmentioning
confidence: 99%